EKSPLORASI ETNOMATEMATIKA DALAM PERMAINAN TRADISIONAL KELERENG DAERAH PADANGSIDIMPUAN SELATAN - Pulungan, Nina Anriani; Adinda, Anita (JURNAL MathEdu (Mathematic Education Journal), 2023)
Ethnomathematics is a breakthrough in the concept of mathematics in which there is a culture associated with mathematics. The presence of mathematics that blends cultures will make a very large contribution or contribution to learning mathematics. The purpose of this study is to identify and describe or describe a mathematical object contained in a traditional game of marbles and what are the benefits of learning mathematics. This research is research qualitative using ethnographic methods. The instruments used by researchers in this study were interviews, documentation, and literature studies directly with the informants. The data analysis techniques used by researchers are data reduction, data presentation, data analysis, and data exposure. The results of the study show that the traditional game of marbles has ethnomathematics related to mathematical concepts including geometric concepts such as circles, balls, triangles, and the, concept of distance. These mathematical concepts can be used to introduce and understand the concepts of geometry and distance through local culture